Tumor cells in multiple myeloma patients inhibit myeloma-reactive T cells through carcinoembryonic antigen-related cell adhesion molecule-6 - Witzens-Harig, Mathias; Hose, Dirk; Jünger, Simone; Pfirschke, Christina; Khandelwal, Nisit; Umansky, Ludmila; Seckinger, Anja; Conrad, Heinke; Brackertz, Bettina; Rème, Thierry; Gueckel, Brigitte; Meißner, Tobias; et al. (Blood, 2013)
Although functionally competent cytotoxic, T cells are frequently observed in malignant diseases, they possess little ability to react against tumor cells. This phenomenon is particularly apparent in multiple myeloma. We here demonstrate that cytotoxic T cells reacted against myeloma antigens when presented by autologous dendritic cells, but not by myeloma cells. We further show by gene expression profiling and flow cytometry that, similar to many other malignant tumors, freshly isolated myeloma cells expressed several carcinoembryonic antigen-related cell adhesion molecules (CEACAMs) at varying proportions. Binding and crosslinking of CEACAM-6 by cytotoxic T cells inhibited their activation and resulted in T-cell unresponsiveness. Blocking of CEACAM-6 on the surface of myeloma cells by specific monoclonal antibodies or CEACAM-6 gene knock down by short interfering RNA restored T-cell reactivity against malignant plasma cells. These findings suggest that CEACAM-6 plays an important role in the regulation of CD8+ T-cell responses against multiple myeloma; therefore, therapeutic targeting of CEACAM-6 may be a promising strategy to improve myeloma immunotherapy.